Comportamiento del consumidor y su influencia en la decisión de compra de calzado, de la población de la ciudad de Mocache, año 2015 - Zambrano Arteaga, Israel Rodolfo (2016)
This research aims to determine the behavior of consumers footwear City Mocache and is based on the description and analysis of current conditions of the consumer market: impacts, development and its influential variables within and outside the environment which they operate. The research question is based on the philosophy of marketing and business aspiration to know the desires and needs no pronounced consumer to generate products and services efficiently, with higher profits and market position, under this premise analyzes a changing industry like footwear. But what is being done in this body to achieve that longed entrepreneurial dream? What is the progress of innovation in this line of business in the city of Mocache? These questions headed the search for answers in their environment through this project, which had a sociological view as independent study, with a unique business ambitions. The research was conducted based on case study methodology, obtaining information from various sources, such as interviews, surveys, observations and literature review. Three variables throughout the investigation were analyzed: (i) the current situation of the footwear industry in the city of Mocache in its various environments, (ii) and conclusive research about footwear market and its stakeholders (iii) the findings in the investigation. This approach favored to conclusions, which seek to determine each of the steps of the purchase decision, and determine the tastes and motivations of consumers Mocacheña society.